1989
DOI: 10.1055/s-2007-1009193
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lactate on Isoproterenol-Induced Lipolysis and β-Adrenoceptors Distribution in Human Fat Cells

Abstract: The influence of lactate on human adipocytes lipolysis and the possible relationship between lactate-induced metabolic effects and beta-adrenoceptor binding sites were investigated. beta-sites were identified in membranes with (125I)-cyanopindolol and in intact cells with (125I)-cyanopindolol and (3H)-CGP 12177. Lactate reduced isoproterenol-induced lipolysis in a dose-response fashion and such inhibition became significant only at 16 mmol/l lactate. Exposure of human fat cells to 16 mmol/l lactate significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…For example, growth hormone is suppressed with somatostatin (18) and is known to have a lipolytic effect (23,24). Also, lactate increased in the present study and this may have contributed to the suppression of lipolysis (25). In any case, the role of glucagon in maintaining basal HGO may need to be reevaluated in a study in which FFA levels are carefully controlled.…”
Section: Discussionmentioning
confidence: 66%
“…For example, growth hormone is suppressed with somatostatin (18) and is known to have a lipolytic effect (23,24). Also, lactate increased in the present study and this may have contributed to the suppression of lipolysis (25). In any case, the role of glucagon in maintaining basal HGO may need to be reevaluated in a study in which FFA levels are carefully controlled.…”
Section: Discussionmentioning
confidence: 66%
“…Both of these studies used concentrations of lactate at the lower end of the dose-response curve that we have observed for recombinant GPR81. De Pergola et al (29) reported in 1989 that lactate could suppress stimulated but not basal lipolysis and that this effect was only significant when lactate reached 16 mM. Lower exposure was not described in the paper.…”
Section: Discussionmentioning
confidence: 88%
“…It has been recognized for many years that lactate inhibits lipolysis both in vivo and in vitro [22][23][24][25]. One can speculate that the decrease in GPR81 expression in adipose tissue could reduce the ability of lactate to inhibit lipolysis and thereby facilitate adipose tissue lipolysis.…”
Section: Resultsmentioning
confidence: 99%